"Kids from here don't go to uni": Considering first in family students' belonging and entitlement within the field of higher education in Australia. (20th December 2020) - O'Shea, Sarah
Abstract: Increasingly students from diverse backgrounds are attending university, many from contexts where accessing higher education is the exception rather than the norm. We know that these learners often have a lower sense of belonging when compared to their second or third generation peers but how this is experienced at an individual level remains unclear. This article explores how current and graduated students articulated their belonging within the higher education environment and how understandings of entitlement played into this conceptualisation. Drawing on Bourdieu's concepts of field and habitus, particularly the notion of cleft habitus (habitus clivé), this article seeks to explore how learners negotiate their status both as university students and graduates . Utilising interviews and surveys conducted with enrolled and graduated first in family learners, the focus is on those who are regarded as successful in the sense of meritocratic achievements and degree conferral. This richly descriptive data points to the emotional undercurrents and relational complexity that attending university can have for those with no generational biographical belonging to this environment and the ways in which learners negotiate between existing and new expectations and norms.